Changes in soil acidity and organic carbon in a sandy typic hapludalf after medium-term pig-slurry and deep-litter application - Brunetto,Gustavo (2012)
Successive applications of liquid swine waste to the soil can increase the contents of total organic carbon and nutrients and change acidity-related soil chemical properties. However, little information is available on the effects of swine waste application in solid form, as of swine deep-litter. The objective of this study was to evaluate alterations of organic carbon and acidity-related properties of a soil after eight years of pig slurry and deep-litter application. In the eighth year of a field experiment established in Braço do Norte, Santa Catarina (SC) on a sandy Typic Hapludalf samples were taken (layers 0-2.5; 2.5-5; 5-10; 10-15; 15-20 and 20-30 cm) from unfertilized plots and plots with pig slurry or deep-litter applications, providing the simple or double rate of N requirement of Zea mays and Avena strigosa in rotation. Soil total organic carbon, water pH, exchangeable Al, Ca and Mg, and cation exchange capacity (CECeffective and CECpH7.0), H+Al, base saturation, and aluminum saturation were measured. The application of pig slurry and deep-litter for eight years increased total organic carbon and CEC in all soil layers. The pig slurry and deep-litter applications reduced active acidity and aluminum saturation and increased base saturation down to a depth of 30 cm. Eight years of pig slurry application did not affect soil acidity.